1) x=2
2) -1/3
4) 1
Пошаговое объяснение:
1) 5(х+2)=2(12-х)
5x+10=24-2x
5x+2x=24-10
7x=14
x=2
2)2(4-3х)+3(х-2)=3
8-6x+3x-6=3
2-3x=3
-3x=3-2
-3x=1
x= -1/3
4) 3(х+1)=2(1-х)+6
3x+3=2-2x+6
3x+3=8-2x
3x+2x=8-3
5x=5
x=1
1) 5(х+2)=2(12-х)5x+10=24-2x5x+2x=24-107x=14x=22) 2(4-3х)+3(х-2)=38-6x+3x-6=32-3x=3-3x=3-2-3x=1x=- 1/34) 3(х+1)=2(1-х)+63x+3=2-2x+63x+3=8-2x3x+2x=8-35x=5x=15) 5,4(0,5х+4)=8,1(4+х)2,7x+21,6=32,4+8,1x2,7x-8,1x=32,4-21,6-5,4x=10,8x=-26) 33х-8(3х-2)=-7х-5(12-3х)33x-24x+16=-7x-60+15x9x+16=8x-609x-8x=-60-16x=-767) 0,15(х - 4) = 9,9 - 0,3(х - 1)0,15x-0,6=9,9-0,3x+0,30,15x-0,6=10,2-0,3x0,15x-0,3x=10,2+0,60,45x=10,8x=248) 3(х+1)=2(1-х)+63x+3=2-2x+63x+3=8-2x3x+2x=8-35x=5x=19) 5,4(0,5х+4)=8,1(4+х)
2,7x+21,6=32,4+8,1x2,7x-8,1x=32,4-21,6-5,4x=10,8x=-2
1) x=2
2) -1/3
4) 1
Пошаговое объяснение:
1) 5(х+2)=2(12-х)
5x+10=24-2x
5x+2x=24-10
7x=14
x=2
2)2(4-3х)+3(х-2)=3
8-6x+3x-6=3
2-3x=3
-3x=3-2
-3x=1
x= -1/3
4) 3(х+1)=2(1-х)+6
3x+3=2-2x+6
3x+3=8-2x
3x+2x=8-3
5x=5
x=1
1) 5(х+2)=2(12-х)
5x+10=24-2x
5x+2x=24-10
7x=14
x=2
2) 2(4-3х)+3(х-2)=3
8-6x+3x-6=3
2-3x=3
-3x=3-2
-3x=1
x=- 1/3
4) 3(х+1)=2(1-х)+6
3x+3=2-2x+6
3x+3=8-2x
3x+2x=8-3
5x=5
x=1
5) 5,4(0,5х+4)=8,1(4+х)
2,7x+21,6=32,4+8,1x
2,7x-8,1x=32,4-21,6
-5,4x=10,8
x=-2
6) 33х-8(3х-2)=-7х-5(12-3х)
33x-24x+16=-7x-60+15x
9x+16=8x-60
9x-8x=-60-16
x=-76
7) 0,15(х - 4) = 9,9 - 0,3(х - 1)
0,15x-0,6=9,9-0,3x+0,3
0,15x-0,6=10,2-0,3x
0,15x-0,3x=10,2+0,6
0,45x=10,8
x=24
8) 3(х+1)=2(1-х)+6
3x+3=2-2x+6
3x+3=8-2x
3x+2x=8-3
5x=5
x=1
9) 5,4(0,5х+4)=8,1(4+х)
2,7x+21,6=32,4+8,1x
2,7x-8,1x=32,4-21,6
-5,4x=10,8
x=-2